Advices for diagnostics of ankylosing spondylitis/axial spondyloarthritis: A review - Nikolay V. Bunchuk; Antonina V. Levshakova (ZAO "Consilium Medicum", 2023)
The article written by a rheumatologist and a radiologist who have long-term experience in diagnostics of ankylosing spondylitis (axial spondylitis), provides advices on rational recognition of these diseases. The first part of the article discusses adequate visualization of the sacroiliac joints and the need for thoughtful consideration of radiological and MRI signs of sacroiliitis, neither of which, taken alone, is pathognomonic. An optimal, from the authors' point of view, algorithm for conducting visualization studies of sacroilial joints is proposed. Numerous situations simulating sacroiliitis are analyzed.